Spectrum of histologic variants of papillary thyroid carcinoma over a period of 5 years- single institutional study - Pravallika Uppala; Renuka I.V.; M. Atchyuta; Naseerudhin Sheik; Garima B.; Sireesha K. (Tropical Journal of Pathology and Microbiology, 2019)
Background: Thyroid carcinoma is the most common malignancy of endocrine system. They arise from two cell types present in the thyroid gland. The endodermally derived follicular cells give rise to papillary, follicular and probably anaplastic carcinomas. The neuroendocrine derived calcitonin producing C cells give rise to medullary carcinomas.Aims and Objectives: To study the different histological variants of papillary thyroid carcinoma (PTC) in thyroidectomy specimens, their frequency, age incidence, sex distribution and presence of metastasis in the regional lymph nodes.Materials and Methods: It was a retrospective study done in the department of Pathology over a period of 5 years from June 2014 – May 2019.Results: A total of 98 cases of papillary thyroid carcinomas were studied out of which 71 cases were of Classic variant, 19 cases of Follicular variant, 2 cases of Papillary Microcarcinoma variant, 1 case each of Cribriform Morular variant, Warthin like variant, Tall cell variant, Columnar cell variant, Oncocytic variant and Non invasive follicular thyroid neoplasm with papillary–like nuclear features (NIFTP).Conclusion: Classic variant of papillary carcinoma thyroid is the most common variant with the highest number of cases followed by follicular and other variants.